دراسة التأثير التثبيطي وتقدير كمية البروتين والتنقية الجزئية لمبروتسين المستخمص من بكتريا mirabilis Proteus المعزولة من عينة إدرار - العزاوي رغد حربي; كزار رباب; رحيم ولاء (Al-Nahrain Journal of Science, 2011)
Proteus mirabilis is one of the most important species of the genus Proteus, and it comes after E. coli in urinary tract infection. The results showed that the isolate of P. mirabilis was resistant to antibiotics of Tetracyclin (30 µg), Amoxicillin (25µg) and Gentamycin (30 µg), While it was sensitive to Ciprofloxacin (5µg). The isolate showed good proticine production that it was inhibit the bacterial growth of other Proteus and other genus like Serratia , Pseudomonas and E.coli, also the extracted proticine from P. mirabilis showed inhibition effect on bacterial growth of Proteus and other genus like Serratia, Pseudomonas and E.col. The amount of protein in this extract was 0.47 mg/ml.The proticin concentration in partially purified by gel filtration chromatography (Sephacryl S1000) was 0.15 mg/ ml and specific activity 513.3 U/ mg protein and with purification folds of 12.1 folds.